BIOLOGICAL FEATURES OF FORMATION OF EXTERIOR AND PRODUCTIVITY OF ADAY HORSES IN THE CONDITIONS OF THE MANGYSHLAK PENINSULA - Kargaeyeva Makpal; Kalashnikov Valery Vasilievich; Yuldashbayev Yusupzhan Artykovich; Mongush Sayana Darzhaevna; Dzhunisov Askar; Alikhanov Oralbek; Yusupbayev Zhaxylyk (Scientific Journal of Pedagogy and Economics, 2020)
It is established that milk mares of the Kazakh horse of the Aday breed have on average live weight of 389.2 kg, height at the withers of 139.2 cm, an oblique body length of 142.1 cm, a chest girth of 167.6 cm and a metacarpus girth of 17.5 cm. Mares of the Kazakh breed of the Mangystau population surpass in the live weight and body measurements the peers of Aday offspring. Namely, the live weight was 415.3 kg, the height at withers – 140.9 cm, the oblique body length – 143.4 cm, the chest girth – 170.5 cm and the metacarpus girth - 18.3 cm. In general, mares of the Kazakh horse of the Aday offspring are inferior to the minimum requirements for animals of the elite class in height at withers, the chest and metacarpus girths. At the same time, 90% of mares correspond to the 1 quality class. In stallions – producers of the Kazakh horses of the Aday offspring, the live weight averaged 438.7 kg, and in stud horses the Mangystau population – 449,8 kg. Body measurements in Aday horses were 145.2-147.5-169.8-18.5 cm, in the Mangystau population – 145.6-148.1-172.2-18.5 cm, respectively. Some regularities of growth and development of foals from birth to 30 months of age are established. A scale for the development of young Aday horses has been developed.